Pruning impacts on rot-shoot growth, biochemical and physiological changes of bougainvillea glabra - Saifuddin, M.; Jahirul, M.I.; Moneruzzaman, K.M.; Sattar, M.A.; Osman, Normaniza; Hossain, A.B.M.S. (2010)
The effects of different pruning on Bougainvillea plants was studied focusing on chlorophyll a & b, quantum yield, sugar content, biomass, stomatal conductance, and flowering process factors. Results on frequent pruning of Bougainvillea glabra plants gave the highest quantum yield, chlorophyll a and b, and maximum flower initiation per plant compared to those of non-pruning plants. Though the sugar content in pruned plants decreased, probably due to the prolonged vegetative phase, flowering process continues and developed new flower shoots. Minimum branch fresh weight and low potassium content were observed in complete pruning plants. The observations also indicated that different pruning treatments modify the root and shoot initiation, which affects the physiological and biochemical content of plants. In the case of the completed pruning, plant maintain a minimum shoot growth rate due to the low availability of potassium, sugar nutrient and lower root growth. Tertiary branch initiation was found to be more effective in the non-pruning condition. The above findings have given a better understanding of the effects of different pruning on the growth and development of the Bougainvillea glabra. Hence, it is suggested that frequent pruning can be used to maintain plant growth and flower shoot initiation.